The Interceptive Dialogue between Musa and Al-Khidr in Surat Al-Kahf (Objective Study) (Journal of the College of Basic Education, 2022)
Thanks to God، the deity of the world، and peace & prayer be upon the best prophet and his relatives & friends. The interpretation of Holy Koran attains a great interest from interpreters regarding revealing its meanings، getting its intentions through an analytical objective study that varies and expands cross time with the change of its trends. with shedding light upon the significance of the koranic terms and the exceeding care it deserves concerning study and research of the interpretative denotation، the verbal and moral connotations included، the parenthetical conversation of the koranic speech- in some ayahs on the tongue of some prophets، especially Mosa (Peace be upon him) in Surat Al-Kahaf، which we think it does not obtain independent study that takes into consideration exploring and reflecting Mosa's (Peace be upon him) three objections، and highlighting its significance in the eloquent expression، and the interpretative denotation it carries in embodying the eloquent meaning in the koranic text، added to the moral and educational references included in the research. The general frame of the research includes three sections preceded by preface the discusses the significance of the topic، questions about the research، its aims، the strategy followed through which a group of supreme morals and basics has been found. In addition، it discusses the inimitability phases in the koranic arrangement for the conversational objection between Mosa & Al-Khudher (Peace be upon them) as an example to be mentioned is that the observer of the Ayahs in Kuran finds that God's wisdom is obvious in devoting people to each other. It is clear that the prophet Mosa (Peace be upon him) shows politeness and loyalty to Al- Khudher with making a basic condition of teaching even after stopping the contract، and taking the permission politely from the teacher to accompany him، and the possibility for the student to make a condition to learn from his teacher. Mosa (Peace be upon him) left the will of conflict and hanged it with patience as much as he could، the teacher clarifies what his learner missed and made use of what he lacked for better than leaving him astonished. Each expression has an intention behind that it gives it a special state، in that، the third event does not contradict legislation، but the first and second events contradict the stable rules of God's legislation. In other words، there is no legislation permits a person to spoil anything related to others، nor killing no guilty person، so sinking the ship (without sinking any person) is easier than killing the boy- who had really been killed. Mosa describes sinking the ship as an incredible thing and killing the boy as a disguising thing. The Holy Ayahs show the justice of Mosa (Peace be upon him)، especially when he greatly and bitterly objected the first two events، because the issue refers to a great spoil in surface، and that is what makes him object. On the contrary، the third event was more merciful in rejecting because the phase of the work refers to charity and; therefore، he uses (if) which refers to sanction.